2006
DOI: 10.1007/s10571-006-9028-x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin Improves the Blood–Brain Barrier Function Through the Expression of Claudin-5

Abstract: AM therefore inhibits the paracellular transport in a BBB in vitro model through claudin-5 overexpression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 39 publications
5
54
0
Order By: Relevance
“…There was no significant change in TEER when we cultured the BBB model up to 10 days after the cells became confluent. The TEER values of the BBB model in our study are comparable to other studies using BMVEC, 22,26 similar to rat BMVEC cells, 24 slightly lower than human BMVEC, 21 but higher than feline BMVEC. 23 Clearly, the TEER is different for different cell types.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…There was no significant change in TEER when we cultured the BBB model up to 10 days after the cells became confluent. The TEER values of the BBB model in our study are comparable to other studies using BMVEC, 22,26 similar to rat BMVEC cells, 24 slightly lower than human BMVEC, 21 but higher than feline BMVEC. 23 Clearly, the TEER is different for different cell types.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, it has been shown that TEER can be modulated by many factors such as cytokines, cAMP, cGMP, nitric oxide, heat and coculturing with other cells. 21,22,[24][25][26] Currently, no specific receptor has been identified for MTf. Although human MTf shares 39% homology with human serum transferrin, 13 TfR is found not to be responsible for MTf transcytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our results indicated that TR-BNBs, which express claudin-5 at cell-cell boundaries, have significantly higher TEER than HUVECs as well as TR-BBBs, which do not express claudin-5 (Ohtsuki et al, 2007). Interestingly, Honda et al reported that adrenomedullin increased the TEER of rat BMEC monolayer through the expression of claudin-5 (Honda et al, 2006). These data and our results indicate that claudin-5 might be a key molecule in maintaining the integrity of TJs in BNB as well as BBB, and malfunction of this molecule might lead to the breakdown of BNB in many autoimmune peripheral neuropathies.…”
Section: Discussionmentioning
confidence: 50%
“…The effect of forskolin on brain endothelial cells was also confirmed by other studies [91,92]. Calcitonin generelated peptide and parathyroid hormone [65] and adrenomedullin [32,93] also clearly demonstrated a cAMPlike effect. The permeability decreasing effect of cAMP analogs was more pronounced in the presence of PDE inhibitors theophylline, methylisobutylxanthine, rolipram, or RO-20-1724 [57].…”
Section: Cyclic Amp Pathwaysupporting
confidence: 74%